Esporte como conteúdo curricular: da formação do pedagogo/a à BNCC - Silva, Leonardo Gervásio da (IEAA - Instituto de Educação, Agricultura e Ambiente (Humaitá), 2022)
The present Course Completion Work - TCC, sought to develop a study focused on training in a degree in Pedagogy, specifically, with regard to the Curriculum component of Physical Education developed in the early years of Elementary School. Its main objective is to analyze how sport is constituted as a curricular content in curricular documents, specifically in the BNCC, taking into account historical elements of the pedagogue's formation to work with this object of knowledge. As a specific objective: a) To understand the elements that make up the formation of the pedagogue to work with the curricular component of Physical Education, specifically with sports activities; b) Describe sport as a curricular content in the early years of Elementary School; c) Present the Educational Policies that formulate the Curricular Component of Physical Education in the initial years; d) To analyze how the BNCC presents sport as curricular content for Elementary School I. For that, we base ourselves on Rey's (2005) qualitative research perspective, which brings an idea of a method that is not established, but is defined and redefined within the its own process, as well as the literature review and document analysis of the curriculum policy instituted by the National Common Curricular Base - BNCC for the development of the Physical Education curricular component in the early years of elementary school. In view of this, we have observed that the initial training of teachers trained in Pedagogy, when produced taking into account sport as a curricular content, does not present the necessary elements for the understanding of this object of knowledge as a condition for thinking about the dynamics of learning. At the same time, the BNCC does not take into account that the subjects who will develop this subject within Elementary School I are professionals/pedagogues trained in motor skills, psychomotricity and playful games and not necessarily teachers trained in Physical Education, the that hinders the development and perception of sport as a descriptive element of health, social and economic relationship.